Determinants of carbon emissions: nexus among carbon emissions, coal, agriculture, trade and innovations - Emir, Firat; Udemba, Edmund Ntom; Philip, Lucy Davou (Springer, 2024)
We study the determinants of India's carbon emissions. India is identified as the third in ranking of global carbon emissions. India's source of energy is mainly fossil fuels of which above average of the energy mix in the country is coal. Considering the position of India in the world emissions, it is paramount to examine the determinants of carbon emissions in the country. We adopt the relevant variables (such as economic growth, coal, agriculture, trade and innovation) and India's data of 1981 to 2019 for clear insight on the key drivers of carbon emissions in India. Our emphasis with regards to the conclusion and policy framing is on the findings from DOLS and granger causality. Findings from DOLS approach show that all the selected variables except the innovation are contributing toward environmental dilapidation through the increase in carbon emissions. Findings from granger causality affirm the findings from DOLS with nexus among the selected variables. This proves that, all explanatory variables are statistically significant determinants of environment and should be considered why framing policies to mitigate pollutions and enhance the environmental state and sustainability.
Keywords: Carbon emissions; Coal; Trade openness; Economic growth; Agriculture; Innovation; India's climate and sustainability goals